2018
DOI: 10.3748/wjg.v24.i2.195
|View full text |Cite
|
Sign up to set email alerts
|

INT-767 improves histopathological features in a diet-inducedob/obmouse model of biopsy-confirmed non-alcoholic steatohepatitis

Abstract: AIMTo characterize the efficacy of the dual FXR/TGR5 receptor agonist INT-767 upon histological endpoints in a rodent model of diet-induced and biopsy-confirmed non-alcoholic steatohepatitis (NASH).METHODSThe effects of INT-767 on histological features of NASH were assessed in two studies using Lepob/ob (ob/ob) NASH mice fed the AMLN diet (high fat with trans-fat, cholesterol and fructose). In a proof-of-concept study, Lepob/ob (ob/ob) NASH mice were first dosed with INT-767 (3 or 10 mg/kg for 8 wk). A second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 35 publications
6
63
0
Order By: Relevance
“…We show that OCA quantitatively reduces hepatic fibrosis as measured by traditional picrosirius red staining, as well as biochemically measured collagen levels. This is in line with the findings of others, who report reduced hepatic collagen content after OCA treatment in chemically induced liver fibrosis and in AMLN diet (high trans‐fat and fructose diet supplemented with 2% cholesterol)–fed ob/ob mice . In addition to the observed reduction in the level of collagen in the liver in the present study, OCA also lowered the degree of reticulation of collagen (of both thin and aggregated collagen fibers) as assessed by multiphoton imaging, a technology that allows the dissection of fibrosis stages in human biopsies .…”
Section: Discussionsupporting
confidence: 93%
“…We show that OCA quantitatively reduces hepatic fibrosis as measured by traditional picrosirius red staining, as well as biochemically measured collagen levels. This is in line with the findings of others, who report reduced hepatic collagen content after OCA treatment in chemically induced liver fibrosis and in AMLN diet (high trans‐fat and fructose diet supplemented with 2% cholesterol)–fed ob/ob mice . In addition to the observed reduction in the level of collagen in the liver in the present study, OCA also lowered the degree of reticulation of collagen (of both thin and aggregated collagen fibers) as assessed by multiphoton imaging, a technology that allows the dissection of fibrosis stages in human biopsies .…”
Section: Discussionsupporting
confidence: 93%
“…BAs may function as signaling molecules through a variety of receptors, such as members of the nuclear receptor superfamily (farnesoid X nuclear receptor [FXR], vitamin D receptor, and pregnane X receptor) and members of the G‐protein‐coupled receptor superfamily (G‐protein‐coupled bile acid receptor 1 and sphingosine‐1‐phosphate receptor 2), among which FXR seems to have evolved as one of most promising avenues for the treatment of metabolic diseases, including NAFLD . A growing body of studies has shown benefits from FXR agonism treatment both in animals and in the clinic . Nonetheless, inhibition of FXR signaling by a specific FXR antagonist or elimination of BAs was also capable of improving hepatic steatosis and NASH in mouse experiments .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of mice with the dual FXR/TGR5 agonist INT-767 induced a restorative intrahepatic macrophage phenotype (Ly6C l°C D206 hi and expression of Retnla and Clec7a). 121 Provision of agonists for FXR and TGR5 have been suggested as potential therapeutics during liver regeneration, where there is an excess bile acid pool 122 in NASH 123 or in cholestatic liver diseases, 124 although some caution is required given the pleiotropic effects of these receptors, such as the role of TGR5 in the development of cholangiocarcinoma. 125 During acute liver failure (ALF), a marked increase in inflammatory macrophages, is observed in areas of necrosis.…”
Section: Immune Cell Interventionmentioning
confidence: 99%